PSVII-18 Heat exposure inhibits the proliferation and expansion of porcine intestinal epithelial cells and stem cells by down-regulating the Wnt/β-catenin pathway. (7th December 2018) - Zhou, J; Li, X; Gao, C; Yan, H; Wang, X
Abstract: The imbalance of intestinal epithelial homeostasis under continuous exposure to high-temperature conditions may be related to the disturbance of intestinal epithelial renewal process which derives from intestinal stem cells (ISCs) and is regulated by Wnt/β-catenin pathway. Therefore, two experiments were conducted to explore whether heat exposure could stimulate proliferation, apoptosis and differentiation of IPEC-J2 cells and expansion of ISCs through Wnt/β-catenin pathways. In experiment 1, the IPEC-J2 cells proliferation and apoptosis were determined after exposed to 41°C. MTT and cell count assay showed that there was a fewer (P < 0.05) number of the heat exposure group compared with the control group (37°C) at 72 h, as well as the expression of proliferating cell nuclear antigen (PCNA). And more percentage of apoptotic cells and the expression of Caspase-3 were found (P < 0.05). Moreover, the markers expression of ISCs (Lgr5 and Bmi1), goblet cells (Muc2) and absorptive cells (SI) were reduced (P < 0.05) in comparison with the control group indicates a decline of differentiation ability. The key protein in Wnt/β-catenin pathway of Axis inhibition protein 2 (Axin2) and glycogen synthase kinase 3β (GSK3β) had an increased expression levels (P < 0.05), correspondingly, β-catenin, Cyclin D1 and c-Myc were all significantly decreased (P < 0.05). In experiment 2, fresh crypts isolated from piglets jejunum were cultured in vitro, we found that heat exposure (41°C) inhibited the formation of intestinal organoid and induced its apoptosis. Furthermore, the expression of Lgr5, Bmi1, β-catenin, PCNA, and Cytokeratin 20 in the heat exposure group at 24 h were decreased (P < 0.05), and Caspase-3 was opposite (P < 0.05). These findings showed that heat-induced the decrease of proliferation and differentiation ability and the increase of apoptosis are mediated by the Wnt/β-catenin pathway pathways. Our findings might provide a novel target for the repair of intestinal damage under high temperature environments.